Nanotechnologies and clusters in the spaces of higher dimension emerging research and opportunities - Zhizhin, G. V. (Gennadiĭ Vladimirovich) (Advances in chemical and materials engineering (ACME) book series., 2021)
"This book examines nanotechnologies and clusters in the spaces of higher dimension"--